How successful are U.S. efforts to build capacity in developing countries? : a framework to assess the global train and equip "1206" program - Moroney, Jennifer D. P., 1973-; Grill, Beth.; Hogler, Joe L.; Kennedy-Boudali, Lianne; Paul, Christopher, 1971-; National Defense Research Institute (U.S.); International Security and Defense Policy Center; Rand Corporation; United States. Department of Defense. Office of the Under Secretary of Defense for Policy (Santa Monica, CA : RAND, 2011)
The U.S. government has long worked with allies and partners in a security cooperation context. Assessing the effect of such activities, and particularly how they contribute to U.S. objectives, is extremely important. The Global Train and Equip (3z(B1206(3y (BProgram is a multiagency security cooperation program that would benefit from an improved framework for thinking about, planning for, and implementing security cooperation assessments. The program, established in Section 1206 of the National Defense Authorization Act for Fiscal Year 2006, supports U.S.-led capacity-building activities focused on counterterrorism and stability operations with foreign military partners. The process to develop an assessment framework for the 1206 program began with a series of discussions with policymakers and subject-matter experts to identify current roles, data sources, and assessment processes. These discussions formed the basis for a survey of program stakeholders on the processes, responsibilities, assessment guidance, and skills needed to conduct assessments. An analysis of the survey results revealed the need for formal guidance on the assessment of 1206 projects, gaps in data collection and reporting, unclear roles, and inconsistent levels of communication across the program. However, it also showed that a two-track (short- and longer-term) approach to implementing an assessment framework, closing gaps, and improving coordination would be the best fit for the 1206 Program$1 (Bs structure.s
Introduction -- RAND's Assessment Framework -- Exploring the Options for 1206 Program Assessment: Discussions with Key Stakeholders -- Applying the Framework to the 1206 Program: Results of the Survey -- Conclusions and Recommendations -- Appendix A: The Assessment Survey -- Appendix B: Focused Discussions.
"RAND National Defense Research Institute."
"This research was sponsored by the Office of the Under Secretary of Defense for Policy and conducted within the International Security and Defense Policy Center of the RAND National Defense Research Institute"--Preface.
Includes bibliographical references (p. 67-68).
Also available on the internet via WWW in PDF format.
Keywords: Combined operations (Military science) -- Evaluation; Military assistance, American -- Foreign countries -- Evaluation; Security Assistance Program -- Evaluation; Terrorism -- Prevention -- International cooperation -- Evaluation; United States -- Armed Forces -- Stability operations -- Evaluation; United States -- Military policy -- Evaluation; United States -- Military relations -- Foreign countries